Phosphorus Transfer Behaviors Induced by CaF2–TiO2–CaO Fluxes in EH36 Shipbuilding Steel Subject to High Heat Input Submerged Arc Welding - Zhong, Ming; Li, Tao; Basu, Somnath; Wang, Zhanjun; Wang, Cong (Metallurgical and materials transactions. B, Process metallurgy and materials processing science, 2022)
Phosphorus transfer behavior has been systematically investigated by submerged arc welding of EH36 shipbuilding steel with CaF 2 –TiO 2 –CaO fluxes. Dephosphorization could be induced when the CaO content is higher than 15.7 mass pct; otherwise, phosphorus uptake may occur. Coupling actual welding process with thermodynamic calculations, it is found that the major driving force enabling phosphorus transfer is largely governed by the activity difference between hypothetical P 2 O 5 in the flux and that equilibrated with the weld metal.